Organizational health between perception and practice - Mihoub, Noureddine (Journal of Human Sciences, 2020)
Organizational health is an extended concept for the literature of organizations, it is based on a theoretical basic, and one of the metaphorical metaphors which are used in the late 1960s within the concepts of management and organizational behavior, for the purposes of innovation and change in organizations to achieve their objectives, adapt to the environment, improve their climate for their human resources and reach an effective level. This will-be presented to him in some detail in this research effort to identify its concept, its dimensions related to the job, the internal situation of the organization, and needs of growth and change, in addition to ways to crystallize perception and practice in reality.